The students’ Readiness for E-Learning during Covid-19 in North Maluku - Firmansyah Firmansyah; Magvirah Octasary; Irmawaty Hasyim; Yetty Yetty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The objective of this study was to assess the E-learning readiness of the students in Maluku Utara. The present study used descriptive quantitative in design, aimed to examine the level of E-learning readiness among the students. From three bachelor subgroups, participants were selected using stratified random sampling. Students who had attended virtual classrooms for at least one semester during the Covid-19 Pandemic met the selection criteria. The results showed that during Covid-19 pandemic 59% of the students had ready for E-learning 34,2% neutral and 6,8% were not ready. Most of the participants had provided in internet access, devices used were available and the method used during online class were easy to adapt. The results also evidenced that the students supported two factors "Technological adaptation" and "Internet usage", so improving the technological facilities in this regard can enhance the students' readiness for E-learning. Many students around the world have adapted to online education as a result of the COVID-19 pandemic. Additionally, the majority of participants in this study were well-prepared for E-learning, as demonstrated by the study's findings. So, the university can implement virtual education. However, it is necessary to increase the students' motivation to learn by providing them with the required infrastructure and training courses to learn new skills and soft wares.